Comparing the Prevalence of Polypharmacy and Potential Drug-Drug Interactions in Nursing Homes and in the Community Dwelling Elderly of Emilia Romagna Region - Burato, Sofia; Leonardi, Luca; Antonazzo, Ippazio Cosimo; Raschi, Emanuel; Ajolfi, Chiara; Baraghini, Manuela; Chiarello, Antonella; Delmonte, Valentina; Di Castri, Lucio; Donati, Monia; Fadda, Antonella; Fedele, Daniela; et al. (Frontiers in Pharmacology, 2021)
We aimed at assessing prevalence of polypharmacy and potential drug-drug interactions (DDIs) with clinical relevance in elderly patient on Emilia Romagna area. Both outpatients and residents in nursing homes were assessed, with only partially overlapping strategies. Methods. We defined a list of 190 pairs of potentially interacting drugs, based on clinical literature and availability of therapeutic alternatives. January-June 2018 data on drug use in over 65-years-old were collected from 9 Local Health Authorities of Emilia Romagna: data on community-dwelling subjects were extracted from archives of reimbursed prescriptions, while drug use in a sample of nursing homes was recorded from clinical charts in one index day within the same semester. The frequency of polypharmacy (at least 5 or at least 10 concorrent drugs) and of each DDI was calculated. Results. In line with different rates of polypharmacy (80% vs 16%), the risk of exposure to at least one interaction was 53.7% in nursing homes and 26,4% in outpatients. Among DDIs, in nursing homes antidepressants - anxiolytics (11,9%) ranked first, followed by antidepressants - aspirin (7.4%). In outpatients, ACE-inhibitors – non-steroidal antinflammatory drugs (NSAIDs) reached 7.2% followed by the calcium channel blockers - -blockers (2.4%). Discussion. Polypharmacy and risk of DDIs appeared very different in the two settings, due to both technical and clinical reasons. In order to reduce use of benzodiazepines, NSAIDs, antidepressants and relevant DDIs, (1) defining alternative options for pain relief in elderly outpatients, and (2) implementing non-pharmacological management of insomnia and anxiety in nursing homes should be prioritised.